Research on the Relationship Between the Stiffness of the Suspension of Cars and the Vibration Frequency of the Body (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
In the article, statistical descriptions of the set of values of the stiffnes and vibration frequencies of the suspension of 25 types of cars and their reliability limits were determined, checked the law of the empirical distribution and described them in graphs in the form of a distribution polygon. At the same time, a graphical description of the laws of the theoretical distribution was built, and a comparison with the distribution of the empirical graph was assessed on the norm of approximations and correspondence. At the same time, the correlation coefficient between the stiffness of the suspension and the vibration frequency of the bodies was determined.